Differences in brain activity induced by imagination of real world and online world activities - Ariana Barmayoun; Manfred E. Beutel; Moritz de Greck (Cogent Psychology)
The present study investigated if there are differences in the neural activity of the healthy human brain during the imagination of activities from the real world in comparison to the imagination of activities from the online world. Using functional MRI, healthy subjects were scanned during a monetary incentive delay task (functional localizer of reward regions) and a novel imagination task (imagination of activities from the real and the online world). The contrast “anticipation of reward” > “anticipation of no outcome” revealed significant hemodynamic responses in the bilateral ventral striatum and other reward regions. The right and the left ventral striatum were selected for further region of interest analysis. The contrast “imagination of high interesting real world activities” > “imagination of high interesting online world activities” revealed a significant difference in the left ventral striatum. Furthermore, when comparing the hemodynamic contrast for the real world difference (“imagination of high interesting real world activities” – “imagination of low interesting real world activities”) with the online world difference (“imagination of high interesting online world activities” – “imagination of low interesting online world activities”), the right and the left ventral striatum showed statistically significant results. Our results underline the crucial role of the reward system in the development of interests. Our findings suggest that the imagination of real world activities, independent of their level of interest, activates the reward system more strongly than the imagination of online world activities. Considering the small sample size of our study, our results remain preliminary and need confirmation through further studies.